2022
DOI: 10.1097/bpo.0000000000002046
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Follow-up After Normal Ultrasound Screening of the Hip in Breech Infants

Abstract: Background: Breech presentation is one of the most important risk factors for developmental dysplasia of the hip, and all breech infants should be screened. The necessity of further follow-up of developmental dysplasia of the hip after normal clinical and sonographic screening is a controversial subject. The purpose of this study to identify the incidence of delayed dysplasia in breech infants after normal ultrasound screening and the necessity of further clinical and radiologic follow-up in these patients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Another US study ( 20 ) reported a prevalence of late DDH of 10%. Recently, a Korean study ( 21 ) demonstrated that among 292 breech infants, two patients (0.7%) had delayed radiographic hip dysplasia at 12–24 months' age after normal ultrasound screening. Pan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another US study ( 20 ) reported a prevalence of late DDH of 10%. Recently, a Korean study ( 21 ) demonstrated that among 292 breech infants, two patients (0.7%) had delayed radiographic hip dysplasia at 12–24 months' age after normal ultrasound screening. Pan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) has no single causative factor but is considered a multifactorial trait. Familiar positive history, certain racial predisposition, female gender, firstborn children, tweens, breech presentation, oligohydramnios, and presence of other orthopedic problems like postural deformities, foot deformities, torticollis, and other skeletal and muscular abnormalities are widely accepted as proven risk factors (1,2,3). Latest investigations suggest that prematurity is not a risk factor for DDH, but a rather protective factor for hip development (4).…”
Section: Introductionmentioning
confidence: 99%